Influence of on-board produced hydrogen and three way catalyst on soot nanostructure in Gasoline Direct Injection engines. (August 2017) - Bogarra, M.; Herreros, J.M.; Tsolakis, A.; York, A.P.E.; Millington, P.J.; Martos, F.J.
Abstract: Effectively controlling carbon soot emission from Gasoline Direct Injection (GDI) engines to achieve legislative emission limits is a challenge for both the vehicle manufacturers and researchers. Transmission electron microscopy is a powerful tool for obtaining morphological and nanostructural parameters of carbon soot in Particulate Matter (PM) emissions. These parameters play a significant role in PM emissions control as are affecting filtration efficiency and soot oxidation characteristics. In this paper, a comprehensive analysis of the interlayer spacing, fringe length and fringe tortuosity (curvature) of primary soot particles from GDI engine has been performed. GDI primary particles showed a core-shell structure, similar to diesel soot, with an inner core diameter between 6 and 16 nm and the outer graphene layer between 6 and 13 nm. The soot nanostructure is not significantly modified by changing the fuel injection timing or by introducing EGR and hydrogen in the combustion process. These results are opposed to those obtained from soot emitted in diesel engines where soot nanostructure is affected with changes in engine operating conditions. Furthermore, the three way catalytic converter does not influence soot nanostructure or the soot oxidation characteristics. Graphical abstract: